2023
DOI: 10.5194/egusphere-2023-20
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of a strong volcanic eruption on the summer middle atmosphere in UA-ICON simulations

Abstract: Abstract. Explosive volcanic eruptions emitting large amounts of sulfur can alter the temperature of the lower stratosphere and change the circulation of the middle atmosphere. The dynamical response of the stratosphere to strong volcanic eruptions has been the subject of numerous studies. The impact of volcanic eruptions on the mesosphere is less well understood because of a lack of large eruptions in the satellite era and only sparse observations before that period. Nevertheless, some measurements indicated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The typical interhemispheric coupling pattern in the middle atmospheric temperature field may be triggered by altered planetary wave activity and/or stratospheric warmings, and has also recently been identified in experimental data in the context of a possible Madden-Julian-Oscillation (MJO) signature in the middle atmosphere (Hoffmann et al, 2022). In addition, the dynamical/thermal effects of volcanic eruptions may impact on the interhemispheric coupling pattern (Wallis et al, 2023).…”
Section: Inter-and Intra-hemispheric Couplingmentioning
confidence: 83%
See 1 more Smart Citation
“…The typical interhemispheric coupling pattern in the middle atmospheric temperature field may be triggered by altered planetary wave activity and/or stratospheric warmings, and has also recently been identified in experimental data in the context of a possible Madden-Julian-Oscillation (MJO) signature in the middle atmosphere (Hoffmann et al, 2022). In addition, the dynamical/thermal effects of volcanic eruptions may impact on the interhemispheric coupling pattern (Wallis et al, 2023).…”
Section: Inter-and Intra-hemispheric Couplingmentioning
confidence: 83%
“…It has also been suggested that part of the apparent 11-year solar signature in PMCs in the SBUV record before 2000 may be caused indirectly by the eruptions of the volcanoes El Chichón in 1982 and Mount Pinatubo in 1991 (Hervig et al, 2016). The underlying physical mechanisms are not well understood, and may also involve intra-and inter-hemispheric coupling via gravity waves (Wallis et al, 2023).…”
Section: Solar Effectsmentioning
confidence: 99%
“…The typical interhemispheric coupling pattern in the middle-atmospheric temperature field may be triggered by altered planetary wave activity and/or stratospheric warmings and has also recently been proposed to be present in observational data in the context of a possible Madden-Julian oscillation (MJO) signature in the middle atmosphere (Hoffmann et al, 2022). In addition, it has been suggested that the thermodynamical effects of volcanic eruptions may affect the interhemispheric coupling pattern (Wallis et al, 2023). It is important to note that the underlying mechanisms are not fully understood for the latter two examples.…”
Section: Inter-and Intrahemispheric Couplingmentioning
confidence: 97%
“…It has also been suggested that part of the apparent 11-year solar signature in PMCs in the SBUV record before 2000 may be caused indirectly by the eruptions of the volcanoes of El Chichón in 1982 and Mount Pinatubo in 1991 (Hervig et al, 2016). The underlying physical mechanisms are not well understood and may also involve intra-and interhemispheric coupling via gravity waves (Wallis et al, 2023).…”
Section: Solar Irradiance Effectsmentioning
confidence: 99%